2007
DOI: 10.1063/1.2715748
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence quenching by photoionization and electron transport in a LaAlO3:Ce3+ crystal

Abstract: A combined photoconductivity, absorption, and thermoluminescence study was performed to understand the absence of luminescence from Ce 3+ in LaAlO 3 :Ce 3+ . It is demonstrated that the absence of luminescence is the result of Ce 3+ ionization from the 5d excited states, which are all located in the conduction band. Ce 3+ ionization is accompanied by the formation of several broad absorption and photoconductivity bands, which are assigned to electron traps. A time and temperature dependent optical investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 16 publications
(15 reference statements)
2
27
0
Order By: Relevance
“…A typical TL spectrum contains an asymmetric broadband ranging from 90 to 290 K and peaking at ~135 K, indicating that the traps are distributed over a wide range of energies below the host conduction band in h -EAO. According to previous studies202122, the delocalization energy of the excited electron at 77 K can be determined from the TL creation spectrum, i.e., the plot of TL integrated intensities versus the illumination wavelengths, as shown by the red ball curve in Fig. 3b (Note that the effect of thermally activated ionization is eliminated at 77 K).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A typical TL spectrum contains an asymmetric broadband ranging from 90 to 290 K and peaking at ~135 K, indicating that the traps are distributed over a wide range of energies below the host conduction band in h -EAO. According to previous studies202122, the delocalization energy of the excited electron at 77 K can be determined from the TL creation spectrum, i.e., the plot of TL integrated intensities versus the illumination wavelengths, as shown by the red ball curve in Fig. 3b (Note that the effect of thermally activated ionization is eliminated at 77 K).…”
Section: Resultsmentioning
confidence: 99%
“…3b also contains a higher energy threshold at ~420 nm. The strong electron delocalization in the high-energy region (i.e., 320−420 nm) can be attributed to the autoionizing intermediate states, i.e., the autoionization of 4 f 6 5 d states lying in the host conduction band202122.…”
Section: Discussionmentioning
confidence: 99%
“…It is clearly shown that the optical absorption is increased by the irradiation of UV photons, and decreased by the irradiation of visible light. In the paper that reported a similar increase in absorption induced by UV photon irradiation, the increased absorption was divided into several components [2]. In the present research, it is assumed that the absorption increase by the irradiation of UV photons can be divided into four Gaussian components with peaks at 2.7, 3.5, 4.0, and 4.5 eV, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, in 2007, Kolk et al published a paper about photoconduction evaluation of Ce:LaAlO 3 [9]. In Kolk's paper, they concluded that Ce 3+ emission did not occur in Ce:LaAlO 3 due to the photoionization.…”
Section: Introductionmentioning
confidence: 92%